FORMING A CULTURE OF READING - Kuchkarova Oysha Oltinboyevna (Journals Park Publishing, 2022)
The article provides a brief overview of the ongoing reforms in the country to form a culture of reading in children. The article cites as an example the decisions and laws adopted in the country on reforms in this area.
Keywords: book; reading; sufficient material